Carbon monoxide intoxication: A report of two cases: Prikaz dveh primerov zastrupitve z ogljikovim monoksidom - Hajdinjak, Emina; Markota, Andrej; Strdin Košir, Alenka; Kirbiš, Simona (Acta Medico-Biotechnica, 2021)
Purpose: Here, we describe the application of non–invasive carbon monoxide monitoring for two patients with suspected carbon monoxide intoxication. Case reports: Since signs and symptoms are non–specific, carbon monoxide intoxication is often diagnosed only after other causes of unconsciousness have been excluded. This paper presents two cases of carbon monoxide and alcohol intoxication. From the information available (both patients were found in open spaces, unconscious, with no external signs of injury), it was impossible to infer carbon monoxide intoxication. In both cases, carbon monoxide intoxication was detected by noninvasive carbon monoxide monitoring in accordance with the ABCDE approach for the immediate assessment and treatment of critically ill patients. Other findings (blood pressure, blood sugar, etc.) did not explain the state of either patient. Both patients received oxygen therapy before the determination of carbon monoxide in the arterial blood and both were discharged after 2 days of treatment without short–term neurological sequelae. The source of carbon monoxide in each case was exposure to smoke and automobile exhaust, respectively, with concurrent alcohol intoxication. Conclusion: The use of devices that enable the rapid and noninvasive detection of carbon monoxide can facilitate diagnosis of carbon monoxide intoxication.